Peripheral Inflammatory Hyperalgesia Depends on P2X7 Receptors in Satellite Glial Cells - Neves, Amanda Ferreira; Farias, Felipe Hertzing; de Magalhães, Silviane Fernandes; Araldi, Dionéia; Pagliusi, Marco; Tambeli, Claudia Herrera; Sartori, Cesar Renato; Lotufo, Celina Monteiro da Cruz; Parada, Carlos Amílcar (Frontiers in Physiology, 2020)
Peripheral inflammatory hyperalgesia depends on the sensitization of primary nociceptive neurons. Inflammation drives molecular alterations not only locally but also in the dorsal root ganglion (DRG) where interleukin-1 beta (IL-1β) and purinoceptors are upregulated. Activation of the P2X7 purinoceptors by ATP is essential for IL-1β maturation and release. At the DRG, P2X7R are expressed by satellite glial cells (SGCs) surrounding sensory neurons soma. Although SGCs have no projections outside the sensory ganglia these cells affect pain signaling through intercellular communication. Therefore, here we investigated whether activation of P2X7R by ATP and the subsequent release of IL-1β in DRG participate in peripheral inflammatory hyperalgesia. Immunofluorescent images confirmed the expression of P2X7R and IL-1β in SGCs of the DRG. The function of P2X7R was then verified using a selective antagonist, A-740003, or antisense for P2X7R administered in the L5-DRG. Inflammation was induced by CFA, carrageenan, IL-1β, or PGE2 administered in rat’s hind paw. Blockage of P2X7R at the DRG reduced the mechanical hyperalgesia induced by CFA, and prevented the mechanical hyperalgesia induced by carrageenan or IL-1β, but not PGE2. It was also found an increase in P2X7 mRNA expression at the DRG after peripheral inflammation. IL-1β production was also increased by inflammatory stimuli in vivo and in vitro, using SGC-enriched cultures stimulated with LPS. In LPS-stimulated cultures, activation of P2X7R by BzATP induced the release of IL-1β, which was blocked by A-740003. In summary, our data suggest that peripheral inflammation leads to the activation of P2X7R expressed by SGCs at the DRG. Then, ATP-induced activation of P2X7R mediates the release of IL-1β from SGC. This evidence places the SGC as an active player in the establishment of peripheral inflammatory hyperalgesia and highlights the importance of the events in DRG for the treatment of inflammatory diseases.